2016
DOI: 10.11646/zootaxa.4061.2.6
|View full text |Cite
|
Sign up to set email alerts
|

New records of the genus Diodontus Curtis, 1834 (Hymenoptera: Crabronidae) from Bulgaria, Montenegro and Poland, with a key to Central and Eastern European species

Abstract: First records of Diodontus medius Dahlbom, 1844 and D. insidiosus Spooner, 1938 from Poland, and of D. handlirschi Kohl, 1888 from Bulgaria and Montenegro are provided. An illustrated key for the identification of Central and Eastern European species of the genus Diodontus is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Using morphological characters and keys to European species of Diodontus (Dollfuss et al 2001;Olszewski et al 2016), the females of the two species, described here as new, would be misidentified as D. minutus due to similar colouration and the distance between lateral teeth of clypeal apex being approximately equal to the distance between the lateral tooth and the eye. Males of both new species would be misidentified as D. insidiosus due to similar colouration and nearly straight, narrow mesobasitarsus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using morphological characters and keys to European species of Diodontus (Dollfuss et al 2001;Olszewski et al 2016), the females of the two species, described here as new, would be misidentified as D. minutus due to similar colouration and the distance between lateral teeth of clypeal apex being approximately equal to the distance between the lateral tooth and the eye. Males of both new species would be misidentified as D. insidiosus due to similar colouration and nearly straight, narrow mesobasitarsus.…”
Section: Discussionmentioning
confidence: 99%
“…Recent revisions of the European representatives of Diodontus (Dollfuss et al 2001;Olszewski et al 2016) do not include species described from North Africa and western Asia, therefore, the status of multiple Mediterranean species is not completely clear. An identification key for Diodontus from this region is not available.…”
Section: Introductionmentioning
confidence: 99%
“…At present, a total of 12 accepted species of the genus Diodontus are known in continental Europe [19,27,28]. However, a preliminary analysis of barcoding sequences available from the Barcode of Life Data System (BOLD) has revealed that the Mediterranean complex of species related to D. insidiosus Spooner, 1938, is represented by multiple divergent and geographically restricted mitotypes forming separate Barcode Index Numbers (BINs), which may correspond to undescribed cryptic species [28].…”
Section: Introductionmentioning
confidence: 99%
“…Remarks: Because of morphological similarity (seeBudrys, 1996) and the lack of regional keys, this group is considered to be difficult for identification. Recently,Olszewski et al (2016) keyed Central and Eastern European species whileBudrys et al (2019) keyed the species of D. minutus (Fabricius, 1793) species-group of the Mediterranean region. The later key can be used partially to identify fauna from southern Iran.…”
mentioning
confidence: 99%